Lithium ion secondary battery and separation membrane
By using a specific separation membrane in a lithium-ion secondary battery, the problem of difficult separation of the positive electrode and the negative electrode solvent is solved, and the performance of the lithium-ion secondary battery is improved.
Patent Information
- Application Number
- CN202080098687.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2040-11-18
AI Technical Summary
In lithium-ion secondary batteries, the positive electrode and the negative electrode contain different electrolyte solvents, making it difficult to fully separate the positive electrode and the negative electrode, resulting in a degradation of performance.
Using a separation membrane with a specific average pore size ensures that lithium ions can pass through while solvents are difficult to pass through, thereby achieving separation of solvents between the positive electrode and the negative electrode. The separation membrane consists of a polymer of a compound having two or more polymerizable groups and a lithium ion conductive compound. The weight average molecular weight of the polymer is 800 or more, and the molecular weight of the lithium ion conductive compound is 150 or less.
Effectively separate the solvent in the positive and negative electrodes, and improve the performance of lithium-ion secondary batteries, including improving energy density and extending battery life.
Smart Images

Figure CN116325261B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a lithium ion secondary battery and a separation membrane. Background Art
[0002] In recent years, with the popularity of portable electronic devices, electric vehicles, etc., the performance requirements of secondary batteries represented by lithium ion secondary batteries have been further improved. For example, research is underway to improve the performance of lithium ion secondary batteries by containing electrolytes of different types in the positive and negative electrodes (e.g., Patent Document 1).
[0003] Previous technical literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2001-110447 Summary of the invention
[0006] Technical issues to be solved by the invention
[0007] In a lithium ion secondary battery in which the positive electrode and the negative electrode contain electrolytes of different types, it is important that the solvent contained in the electrolyte is fully separated and not mixed between the positive electrode and the negative electrode. The present inventors considered configuring a separation membrane between the positive electrode and the negative electrode in order to separate the solvent in the electrolyte in such a lithium ion secondary battery. In the separation membrane, lithium ions need to pass through the separation membrane, but the solvent has the property of being difficult to pass through.
[0008] An object of the present invention is to provide a separation membrane having excellent separation ability of the solvents used in a lithium ion secondary battery containing different solvents in the positive electrode mixture layer and the negative electrode mixture layer, and a lithium ion secondary battery including the separation membrane.
[0009] Means for solving technical problems
[0010] The present inventors have found that the solvent contained in the positive electrode mixture layer and the negative electrode mixture layer can be effectively separated by a separation membrane having pores whose average pore diameter is adjusted to a predetermined range, and have completed the present invention.
[0011] One aspect of the present invention provides a lithium ion secondary battery, which comprises a positive electrode mixture layer, a separation membrane and a negative electrode mixture layer in order, wherein the positive electrode mixture layer contains a positive electrode active material, a first lithium salt and a first solvent, the negative electrode mixture layer contains a negative electrode active material, a second lithium salt and a second solvent different from the first solvent, and the separation membrane has an average pore size of More than and less than of pores.
[0012] Another aspect of the present invention provides a separation membrane, which is a separation membrane for being arranged between a positive electrode mixture layer and a negative electrode mixture layer in a lithium ion secondary battery having a positive electrode mixture layer and a negative electrode mixture layer, wherein the positive electrode mixture layer contains a positive electrode active material, a first lithium salt and a first solvent, and the negative electrode mixture layer contains a negative electrode active material, a second lithium salt and a second solvent different from the first solvent, and the separation membrane has an average pore size of More than and less than of pores.
[0013] The separation membrane contains a polymer of a compound having two or more polymerizable groups and a lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group. The weight average molecular weight of the polymer is 800 or more, and the molecular weight of the lithium ion conductive compound can be 150 or less.
[0014] The separation membrane may contain a cross-linked product of polymers having a group represented by the following formula (1).
[0015]
[0016] [Where R 1 represents an alkylene group having 1 to 6 carbon atoms, and * represents a bond. ]
[0017] In the lithium ion secondary battery, the molecular diameters of the first solvent and the second solvent are preferably above.
[0018] Effects of the Invention
[0019] According to the present invention, there can be provided a separation membrane having excellent separation ability of the solvents used in a lithium ion secondary battery containing different solvents in the positive electrode mixture layer and the negative electrode mixture layer, and a lithium ion secondary battery including the separation membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a perspective view showing a lithium ion secondary battery according to one embodiment.
[0021] Figure 2 Yes means Figure 1 1 is an exploded perspective view of one embodiment of an electrode group in a lithium ion secondary battery shown in FIG. DETAILED DESCRIPTION
[0022] Hereinafter, embodiments of the present invention will be described with reference to the drawings as appropriate. However, the present invention is not limited to the following embodiments.
[0023] In this specification, (meth)acrylic acid means acrylic acid or methacrylic acid corresponding thereto. The same applies to other similar expressions such as (meth)acrylate.
[0024] Figure 1 1 is a perspective view showing a lithium ion secondary battery according to one embodiment. Figure 1 As shown, the lithium ion secondary battery 1 involved in one embodiment is a so-called stacked secondary battery, which includes an electrode group 2 and a bag-shaped battery outer body 3 that accommodates the electrode group 2. In the electrode group 2, a positive electrode collector sheet 4 and a negative electrode collector sheet 5 are provided. The positive electrode collector sheet 4 and the negative electrode collector sheet 5 protrude from the inside of the battery outer body 3 to the outside, respectively, so that the positive electrode collector and the negative electrode collector (which will be described in detail later) can be electrically connected to the outside of the lithium ion secondary battery 1. In another embodiment, the lithium ion secondary battery 1 can be in a shape other than a stacked type (coin-shaped, cylindrical, etc.).
[0025] The battery exterior body 3 may be a container formed of a laminated film, for example, a polymer film such as polyethylene terephthalate (PET) film, a metal foil such as aluminum, copper, stainless steel, and a sealant layer such as polypropylene laminated in this order.
[0026] Figure 2 Yes means Figure 1 FIG. 1 is an exploded perspective view of an embodiment of an electrode group 2 in a lithium-ion secondary battery 1. Figure 2 As shown, the electrode group 2 according to the present embodiment includes a positive electrode 6, a separator 7, and a negative electrode 8 in this order. The positive electrode 6 includes a positive electrode collector 9 and a positive electrode mixture layer 10 provided on the positive electrode collector 9. A positive electrode collector sheet 4 is provided in the positive electrode collector 9. The negative electrode 8 includes a negative electrode collector 11 and a negative electrode mixture layer 12 provided on the negative electrode collector 11. A negative electrode collector sheet 5 is provided in the negative electrode collector 11.
[0027] The positive electrode current collector 9 is formed of, for example, aluminum, titanium, stainless steel, nickel, calcined carbon, conductive polymer, conductive glass, etc. The thickness of the positive electrode current collector 9 may be, for example, 1 μm or more and 50 μm or less.
[0028] The negative electrode current collector 11 is made of, for example, copper, stainless steel, nickel, aluminum, titanium, calcined carbon, conductive polymer, conductive glass, aluminum-cadmium alloy, etc. The thickness of the negative electrode current collector 11 may be, for example, 1 μm or more and 50 μm or less.
[0029] In one embodiment, the positive electrode mixture layer 10 contains a positive electrode active material, a lithium salt (first lithium salt), and a solvent (first solvent).
[0030] The positive electrode active material may be, for example, lithium oxide. Examples of lithium oxide include Lix CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1-y M y O z , Li x Mn2O4 and Li x Mn 2-y M y O4 (In each formula, M represents at least one element selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Cu, Zn, Al, Cr, Pb, Sb, V and B (wherein M is an element different from other elements in each formula). x = 0 to 1.2, y = 0 to 0.9, z = 2.0 to 2.3.) Li x Ni 1-y M y O z The lithium oxide represented may be Li x Ni 1-(y1+y2) Co y1 Mn y2 O z (where x and z are the same as above, y1 = 0 to 0.9, y2 = 0 to 0.9, and y1 + y2 = 0 to 0.9.) For example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2.Li x Ni 1-y M y O z The lithium oxide represented may be Li x Ni 1-(y3+y4) Co y3 Al y4 O z (where x and z are the same as above, y3 = 0 to 0.9, y4 = 0 to 0.9, and y3 + y4 = 0 to 0.9.) For example, it can be LiNi0.8 Co 0.15 Al 0.05 O2.
[0031] The positive electrode active material may be a lithium phosphate. Examples of lithium phosphates include lithium manganese phosphate (LiMnPO4), lithium iron phosphate (LiFePO4), lithium cobalt phosphate (LiCoPO4) and lithium vanadium phosphate (Li3V2(PO4)3). The positive electrode active materials may be used alone or in combination of two or more.
[0032] The content of the positive electrode active material can be 70 mass % or more, 80 mass % or more, or 85 mass % or more based on the total amount of the positive electrode mixture layer. The content of the positive electrode active material can be 95 mass % or less, 92 mass % or less, or 90 mass % or less based on the total amount of the positive electrode mixture layer.
[0033] The first lithium salt can be, for example, at least one selected from the group consisting of LiPF6, LiBF4, LiClO4, LiNO3, LiB(C6H5)4, LiCH3SO3, CF3SO2OLi, LiN(SO2F)2 (LiFSI, lithium bis(fluorosulfonyl)imide), LiN(SO2CF3)2 (LiTFSI, lithium bis(trifluoromethanesulfonyl)imide) and LiN(SO2CF2CF3)2.
[0034] The content of the first lithium salt may be 0.5 mol / L or more, 0.7 mol / L or more, or 0.8 mol / L or less, or 1.5 mol / L or less, 1.3 mol / L or less, or 1.2 mol / L or less, based on the total amount of the first solvent.
[0035] The first solvent is a solvent for dissolving the first lithium salt. The first solvent preferably has a molecular diameter of Thus, in the lithium ion secondary battery 1 , the first solvent and the second solvent described below can be easily separated by the separation membrane 7 .
[0036] From the viewpoint of making it easier to separate the solvent by the separation membrane 7, the molecular diameter of the first solvent is preferably More preferably The above, more preferably From the viewpoint of easy stirring when the lithium salt is dissolved, the molecular diameter of the first solvent is preferably The following are more preferably The following is further preferably the following.
[0037] The molecular diameter of the first solvent can be calculated based on theoretical bond lengths by finding the most stable structure of the solvent using density functional theory (DFT), which is one type of quantum chemical calculation.
[0038] As the molecular diameter is Examples of the first solvent include fluorinated phosphoric acid esters such as ethylene glycol dimethyl ether represented by the following formula (2) and tris(1H,1H,5H-octafluoropentyl)phosphate.
[0039] R 21 O-(CH2CH2O) k1 -R 22 (2)
[0040] [In formula (2), R 21 and R 22 Each independently represents an alkyl group having 1 to 4 carbon atoms, and k1 represents an integer of 4 to 6.]
[0041] More specifically, the glycol dimethyl ether may be tetraglycol dimethyl ether (k1=4), pentaglycol dimethyl ether (k1=5), or hexaglycol dimethyl ether (k1=6).
[0042] The first solvent may be, in addition to the above-mentioned solvents, cyclic carbonates such as ethylene carbonate, propylene carbonate, vinyl carbonate, vinyl ethylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, etc., chain carbonates such as dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, etc., cyclic esters such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, ε-caprolactone, γ-valerolactone, tetrahydrofuran, 1,3-dioxane, dimethoxyethane, diethoxyethane, methoxyethoxyethane, phosphoric acid triesters, nitriles such as acetonitrile, benzonitrile, adiponitrile, glutaronitrile, chain sulfones such as dimethyl sulfone, diethyl sulfone, cyclic sulfones such as cyclopentane, cyclic sulfonates such as propane sultone, etc. From the viewpoint of improving the oxidation resistance of the positive electrode mixture layer 10, the first solvent may be a solvent having oxidation resistance such as acetonitrile and ethylene carbonate.
[0043] As the first solvent, the above-mentioned solvents may be used alone or in combination of two or more.
[0044] The content of the first solvent contained in the positive electrode mixture layer 10 can be appropriately set within a range capable of dissolving the first lithium salt, and can be, for example, 10 mass % or more and 80 mass % or less based on the total amount of the positive electrode mixture layer.
[0045] The positive electrode mixture layer 10 may further contain a binder and a conductive material as other components.
[0046] The binder may be a polymer containing at least one selected from the group consisting of tetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, acrylic acid, maleic acid, ethyl methacrylate, methyl methacrylate and acrylonitrile as a monomer unit, a rubber such as styrene-butadiene rubber, isoprene rubber, acrylic rubber, etc. The binder is preferably polyvinylidene fluoride or a copolymer containing hexafluoropropylene and vinylidene fluoride as monomer units.
[0047] The binder content can be 0.3 mass %, 0.5 mass %, 1 mass % or 1.5 mass % or more, based on the total amount of the positive electrode mixture layer, and can also be 10 mass %, 8 mass %, 6 mass % or 4 mass % or less.
[0048] The conductive material may be a carbon material such as carbon black, acetylene black, graphite, carbon fiber, carbon nanotube, etc. These conductive materials may be used alone or in combination of two or more.
[0049] The content of the conductive material is based on the total amount of the positive electrode mixture layer, and can be 0.1 mass % or more, 1 mass % or more, or 3 mass % or more. From the perspective of the increase in the volume of the positive electrode 6 and the resulting decrease in the energy density of the lithium ion secondary battery 1, the content of the conductive material is preferably 15 mass % or less, more preferably 10 mass % or less, and further preferably 8 mass % or less, based on the total amount of the positive electrode mixture layer.
[0050] The thickness of the positive electrode mixture layer 10 may be 5 μm or more, 10 μm or more, 15 μm or more, or 20 μm or less, or 100 μm or less, 80 μm or less, 70 μm or less, or 50 μm or less.
[0051] In one embodiment, the negative electrode mixture layer 12 contains a negative electrode active material, a lithium salt (a second lithium salt), and a solvent (a second solvent).
[0052] The negative electrode active material can use materials commonly used in the field of energy devices. Specific examples of the negative electrode active material include metallic lithium, lithium titanate (Li4Ti5O 12), lithium alloys or other metal compounds, carbon materials, metal complexes, organic polymer compounds, etc. These negative electrode active materials can be used alone or in combination of two or more. As carbon materials, natural graphite (phosphonium flake graphite, etc.), graphite such as artificial graphite (graphite), amorphous carbon, carbon fiber, and carbon black such as acetylene black, stove black, channel black, furnace black, lamp black, thermal black, etc. can be cited. From the perspective of obtaining a larger theoretical capacity (for example, 500 to 1500Ah / kg), the negative electrode active material can be a negative electrode active material containing silicon as a constituent element, a negative electrode active material containing tin as a constituent element, etc. Among these, the negative electrode active material can be a negative electrode active material containing silicon as a constituent element.
[0053] The negative electrode active material containing silicon as a constituent element may be an alloy containing silicon as a constituent element, for example, an alloy containing silicon and at least one selected from the group consisting of nickel, copper, iron, cobalt, manganese, zinc, indium, silver, titanium, germanium, bismuth, antimony and chromium as a constituent element. The negative electrode active material containing silicon as a constituent element may be an oxide, a nitride or a carbide, specifically, for example, silicon oxide such as SiO, SiO2, LiSiO, silicon nitride such as Si3N4, Si2N2O, silicon carbide such as SiC, etc.
[0054] The content of the negative electrode active material can be 60% by mass or more, 65% by mass or more, or 70% by mass or more based on the total amount of the negative electrode mixture layer. The content of the negative electrode active material can be 99% by mass or less, 95% by mass or less, or 90% by mass or less based on the total amount of the negative electrode mixture layer.
[0055] The type and content of the second lithium salt may be the same as those of the first lithium salt contained in the positive electrode mixture layer 10. The second lithium salt may be the same as or different from the first lithium salt.
[0056] The second solvent is a solvent for dissolving the second lithium salt. As the second solvent, the same solvent as the first solvent can be used, but a solvent different from the first solvent can be used. Thus, since solvents suitable for the positive electrode 6 and the negative electrode 8 can be used, respectively, various properties of the lithium ion secondary battery 1 such as energy density and life can be improved.
[0057] The second solvent preferably has a molecular diameter of The molecular diameter is Specific examples of the above solvents are as described above. From the viewpoint of suppressing the reductive decomposition of the second solvent contained in the negative electrode mixture layer 12, the second solvent may be a solvent having anti-reduction properties such as γ-butyrolactone and tetrahydrofuran. The second solvent may be used alone or in combination of two or more of the above solvents.
[0058] The content of the second solvent contained in the negative electrode mixture layer 12 can be appropriately set within a range capable of dissolving the second lithium salt, and can be, for example, 10 mass % or more and 80 mass % or less based on the total amount of the negative electrode mixture layer.
[0059] The negative electrode mixture layer 12 may further contain a binder and a conductive material as other components. The types and contents of the binder and the conductive material may be the same as those of the positive electrode mixture layer 10 .
[0060] The thickness of the negative electrode mixture layer 12 may be 10 μm or more, 15 μm or more, or 20 μm or less, or 100 μm or less, 80 μm or less, 70 μm or less, 50 μm or less, 40 μm or less, or 30 μm or less.
[0061] In the lithium ion secondary battery 1, the separation membrane 7 is a separation membrane for being arranged between the positive electrode mixture layer 10 and the negative electrode mixture layer 12. The separation membrane has a function of separating the first solvent and the second solvent contained in the positive electrode mixture layer 10 and the negative electrode mixture layer 12 from each other so that they are not mixed. The separation membrane 7 can transfer lithium ions.
[0062] The separation membrane 7 is a porous body having a porous structure and has an average pore size of More than and less than of pores.
[0063] From the viewpoint of not hindering the movement of lithium ions, the average pore size of the separation membrane 7 is Above, preferably More preferably The above, more preferably From the viewpoint of further improving the separation ability of the solvent, the average pore size of the separation membrane 7 is smaller than Preferably The following are more preferably The following is further preferably The average pore diameter of the separation membrane 7 can be measured by a gas adsorption method using argon gas, and more specifically, the average pore diameter can be calculated from the amount of argon gas adsorbed to the pores of the separation membrane 7 .
[0064] In one embodiment (first embodiment), the separation membrane 7 having an average pore size is a separation membrane comprising: a polymer of a compound having two or more polymerizable groups; and a lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group, wherein the weight average molecular weight of the polymer is 800 or more, and the molecular weight of the lithium ion conductive compound is 150 or less. In this separation membrane, by adjusting the weight average molecular weight of the polymer and the molecular weight of the lithium ion conductive compound to the above ranges, the average pore size of the separation membrane 7 can be adjusted to More than and less than
[0065] The polymerizable group in the compound having two or more polymerizable groups (hereinafter also referred to as "polymerizable compound") is, for example, a group containing an ethylenically unsaturated bond. The polymerizable group may be a free radical polymerizable group, or may be a vinyl group, an allyl group, a styryl group, an alkenyl group, an alkenylene group, a (meth)acryloyl group, a maleimide group, or the like.
[0066] In one embodiment, the polymerizable compound may be a multifunctional (meth)acrylate (poly (meth)acrylate). Examples of the multifunctional (meth)acrylate include polyalkylene glycol di (meth)acrylates such as polyethylene glycol di (meth)acrylate.
[0067] In the separation membrane of the first embodiment, the weight average molecular weight of the polymer of the polymerizable compound is 800 or more. More than and less than From the viewpoint of increasing the average pore size of the separation membrane 7 within a range of , the weight average molecular weight of the polymer is preferably 900 or more, 1000 or more, 3000 or more, 5000 or more, 7000 or more, or 9000 or more. More than and less than The weight average molecular weight of the polymer is preferably 200,000 or less, more preferably 100,000 or less, and further preferably 50,000 or less, from the viewpoint of reducing the average pore size of the separation membrane 7 within a range of . The weight average molecular weight is measured by gel permeation chromatography (GPC) and is a value obtained by conversion from a standard polystyrene calibration curve (the same below).
[0068] From the viewpoint of membrane strength, the content of the polymer of the polymerizable compound is preferably 5% by mass or more, more preferably 15% by mass or more, and further preferably 30% by mass or more based on the total amount of the separation membrane. From the viewpoint of being difficult to hinder the movement of lithium ions, the content of the polymer of the polymerizable compound is preferably 95% by mass or less, more preferably 85% by mass or less, and further preferably 80% by mass or less based on the total amount of the separation membrane.
[0069] The lithium ion conductive compound refers to a compound having lithium ion conductivity, and refers to a compound having the property of being able to conduct lithium ions from the lithium salt in the presence of a lithium salt. Whether the compound can conduct lithium ions can be confirmed by measuring the ion conductivity of the compound. If the peak of the ion conductivity measured when 1 to 40 mass % of a lithium salt is added to the compound is 1×10 -6 S / cm or more, the compound can be regarded as having lithium ion conductivity.
[0070] The lithium ion conductive compound has at least one group selected from the group consisting of a carbonyl group and a chain ether group.
[0071] In one embodiment, the lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group may be a carbonate ester such as a chain carbonate ester such as dimethyl carbonate, diethyl carbonate, or ethyl methyl carbonate.
[0072] In another embodiment, the lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group may be ethylene glycol dimethyl ether represented by the following formula (3).
[0073] R 23 O-(CH2CH2O) k2 -R 24 (3)
[0074] [In formula (3), R 23 and R 24 Each independently represents an alkyl group having 1 to 4 carbon atoms, and k2 represents an integer of 1 to 6.]
[0075] More specifically, ethylene glycol dimethyl ether can be monoethylene glycol dimethyl ether (k2=1), diethylene glycol dimethyl ether (k2=2), triethylene glycol dimethyl ether (k2=3), tetraethylene glycol dimethyl ether (k2=4), pentaethylene glycol dimethyl ether (k2=5), and hexaethylene glycol dimethyl ether (k2=6).
[0076] In the separation membrane of the first embodiment, the molecular weight of the lithium ion conductive compound is 150 or less. More than and less than From the viewpoint of increasing the average pore diameter of the separation membrane 7 within a range of , the molecular weight of the lithium ion conductive compound is preferably 10 or more, more preferably 20 or more, and further preferably 30 or more. More than and less than From the viewpoint of reducing the average pore diameter of the separation membrane 7 within a range of , the molecular weight of the lithium ion conductive compound is preferably 145 or less, more preferably 140 or less, and further preferably 135 or less.
[0077] From the viewpoint of further improving the ion conductivity of the separation membrane 7, the content of the lithium ion conductive compound is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on the total amount of the separation membrane. From the viewpoint of film forming properties, the content of the lithium ion conductive compound is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on the total amount of the separation membrane.
[0078] The separation membrane involved in the first embodiment may further contain a lithium salt (third lithium salt), a polymerization initiator, etc. as other components. As the third lithium salt, the same lithium salt as the first lithium salt can be used. The third lithium salt may be the same as or different from the first and second lithium salts.
[0079] The content of the third lithium salt may be 1% by mass or more, 1.5% by mass or more, or 2% by mass or less, based on the total amount of the separation membrane. The content of the polymerization initiator may be 0.1% by mass or more, or 10% by mass or less, based on the total amount of the separation membrane.
[0080] In another embodiment (second embodiment), the separation membrane 7 having the average pore size is a separation membrane containing a cross-linked product of polymers having groups represented by the following formula (1). In the separation membrane, the polymer having groups represented by the following formula (1) is cross-linked by using lithium ions present in the lithium ion secondary battery 1 or in the separation membrane 7 as an initiator, so that the groups represented by the formula (1) are bonded to each other to form pores having the above average pore size. The average pore size of the separation membrane 7 can be adjusted by adjusting R in the following formula (1). 1 The adjustment is made based on the number of carbon atoms represented.
[0081]
[0082] In formula (1), R 1 represents an alkylene group having 1 to 6 carbon atoms, and * represents a bond.
[0083] The polymer having a group represented by formula (1) may be, for example, a polymer represented by the following formula (4).
[0084]
[0085] In formula (4), R 1 With R in formula (1) 1 has the same meaning, R 11 represents a linear or branched alkylene group or a single bond, and r represents an integer of 2 or greater.
[0086] In formula (1) or formula (4), More than and less than From the perspective of increasing the average pore size of the separation membrane 7 within a range of 1 The number of carbon atoms of the alkylene group represented by is preferably 2 or more or 3 or more. More than and less than From the viewpoint of reducing the average pore size of the separation membrane 7 within a range of 5 to 4, it is preferably 5 or less or 4 or less.
[0087] In formula (4), R 11 The number of carbon atoms of the alkylene group represented may be, for example, 2 or more, or 5 or less. r may be, for example, 5 or more, or 20 or less.
[0088] Examples of the polymer having a group represented by formula (1) include polyglycidyl (meth)acrylate and poly (3-ethyloxetan-3-yl) methyl (meth)acrylate.
[0089] The weight average molecular weight of the polymer having a group represented by formula (1) may be 900 or more, 1000 or more, or 3000 or more, or 200000 or less, 100000 or less, or 50000 or less.
[0090] From the viewpoint of membrane strength, the content of crosslinked polymers having groups represented by formula (1) is preferably 5% by mass or more, more preferably 15% by mass or more, and further preferably 30% by mass or more, based on the total amount of the separation membrane. From the viewpoint of being difficult to hinder the movement of lithium ions, the content of the crosslinked polymer is preferably 95% by mass or less, more preferably 85% by mass or less, and further preferably 80% by mass or less, based on the total amount of the separation membrane.
[0091] The separation membrane according to the second embodiment may further contain a lithium salt (third lithium salt), a polymerization initiator, etc. as other components. The types of the third lithium salt and the polymerization initiator and their contents in the separation membrane 7 may be the same as those of the separation membrane according to the first embodiment.
[0092] From the viewpoint of further improving the separation capability of the separation membrane 7, the thickness of the separation membrane 7 involved in the above-described embodiment is 100 μm or more, preferably 200 μm or more or 500 μm or more. From the viewpoint of improving the energy density of the separation membrane 7, the thickness of the separation membrane 7 is preferably 800 μm or less, 600 μm or less or 400 μm or less.
[0093] Next, a method for manufacturing a lithium ion secondary battery 1 is described. The method for manufacturing a lithium ion secondary battery 1 according to one embodiment includes: a step of obtaining a positive electrode 6 having a positive electrode mixture layer 10 containing a positive electrode active material, a first lithium salt, and a first solvent; a step of obtaining a negative electrode 8 having a negative electrode mixture layer 12 containing a negative electrode active material, a second lithium salt, and a second solvent different from the first solvent; and a step of providing a separation membrane 7 between the positive electrode 6 and the negative electrode 8. The order of the steps is arbitrary.
[0094] In the above-mentioned production method, specific aspects of the positive electrode active material, the first lithium salt, the first solvent, the negative electrode active material, the second lithium salt, the second solvent, and the separation membrane 7 are as described above.
[0095] In the process of obtaining the positive electrode and the process of obtaining the negative electrode, the positive electrode 6 and the negative electrode 8 can be obtained by a known method. For example, a material used for the positive electrode mixture layer 10 or the negative electrode mixture layer 12 is dispersed in an appropriate amount of a dispersion medium using a mixer, a disperser, etc. to obtain a slurry-like positive electrode mixture or a negative electrode mixture. Then, the positive electrode mixture or the negative electrode mixture is applied to the positive electrode collector 9 or the negative electrode collector 11 using a scraper method, an immersion method, a spraying method, etc., and the dispersion medium is volatilized to obtain the positive electrode 6 and the negative electrode 8. At this time, the dispersion medium can be water, N-methyl-2-pyrrolidone (NMP), etc.
[0096] The step of providing the separation membrane 7 between the positive electrode 6 and the negative electrode 8 may include the step of manufacturing the separation membrane 7. In one embodiment, the step of manufacturing the separation membrane 7 includes the step of preparing a slurry containing a material of the separation membrane 7 and forming the slurry into a film.
[0097] In the case of the separation membrane according to the first embodiment, the slurry contains: a compound having two or more polymerizable groups (polymerizable compound); and a lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group. The polymerizable compound and the lithium ion conductive compound are as described above.
[0098] The slurry may further contain the third lithium salt. The content of the third lithium salt may be 1 mass % or more, 3 mass % or more, or 5 mass % or less, or 30 mass % or less, 25 mass % or less, or 20 mass % or less, based on the total amount of the slurry.
[0099] The slurry may further contain a polymerization initiator. This allows the polymerizable compound to be appropriately polymerized, and a separation membrane can be appropriately prepared from the slurry. The polymerization initiator may be a thermal polymerization initiator or a photopolymerization initiator, and can be appropriately selected according to the purpose.
[0100] Examples of the thermal polymerization initiator include azobisisobutyronitrile and azobis(2-methylbutyronitrile).
[0101] Examples of the photopolymerization initiator include 2-hydroxy-2-methyl-1-phenylpropanol and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.
[0102] The content of the polymerization initiator can be 0.5 mass % or more, 1 mass % or more, 10 mass % or more, or 20 mass % or less, based on the total amount of the slurry, or 50 mass % or less, 40 mass % or less, 30 mass % or less, 10 mass % or less, 5 mass % or less, or 3 mass % or less.
[0103] The method of forming the slurry into a film is, for example, to set a frame of any size on one surface of a substrate such as a PET sheet and pour the slurry into it. Alternatively, the slurry can be formed into a film by applying the slurry on one surface of the substrate using a doctor blade method, a dipping method, a spraying method, or the like.
[0104] The step of manufacturing the separation membrane 7 may further include a step of polymerizing a compound having two or more polymerizable groups contained in the slurry formed into a membrane after the slurry is formed into a membrane. In this way, the separation membrane according to the first embodiment is manufactured.
[0105] The method of polymerizing the polymerizable compound is a method of applying heat under predetermined conditions when the slurry contains a thermal polymerization initiator. The heating temperature is, for example, 50 to 90° C. The heating time can be appropriately adjusted according to the heating temperature, for example, 1 minute to 2 hours.
[0106] The method of polymerizing the polymerizable compound is a method of irradiating light under predetermined conditions when the slurry contains a photopolymerization initiator. In one embodiment, the polymerizable compound can be polymerized by irradiating light (ultraviolet light) having a wavelength within the range of 200 to 400 nm.
[0107] When the separation membrane 7 is the separation membrane according to the second embodiment, the slurry used in the step of producing the separation membrane 7 may contain a polymer having a group represented by the above formula (1).
[0108] In this case, the slurry may further contain a third lithium salt and / or a polymerization initiator. The types of the third lithium salt and the polymerization initiator and the contents thereof in the slurry may be the same as those in the separation membrane according to the first embodiment.
[0109] The method of forming the slurry into a membrane may be the same as that in the case of the separation membrane according to the first embodiment.
[0110] When the separation membrane 7 is the separation membrane according to the second embodiment, the step of manufacturing the separation membrane 7 may further include a step of cross-linking the polymer having the group represented by formula (1) contained in the slurry formed into a membrane. In this way, the separation membrane according to the second embodiment is manufactured.
[0111] The method of cross-linking the polymer can be carried out in the same manner as the step of polymerizing the compound having two or more polymerizable groups in the step of manufacturing the separation membrane 7 involved in the first embodiment. At this time, the lithium salt contained in the slurry plays the role of a cross-linking agent, and the polymers having the groups represented by formula (1) are cross-linked with each other to form a cross-linked product.
[0112] In the step of providing the separator 7 between the positive electrode 6 and the negative electrode 8, the positive electrode 6, the separator 7, and the negative electrode 8 are then stacked, for example, using a stacking plate. Thus, an electrode group 2 including the positive electrode 6, the negative electrode 8, and the separator 7 provided between the positive electrode 6 and the negative electrode 8 can be obtained. Then, the lithium ion secondary battery 1 can be obtained by housing the electrode group 2 in the battery exterior body 3.
[0113] Example
[0114] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0115] [Example 1]
[0116] 6.0 g of polyethylene glycol diacrylate represented by the following formula (2) (where n=14, (product name: NKEster A-600, manufactured by SHIN-NAKAMURA CHEMICAL CO., LTD.)), 4.0 g of diethyl carbonate (molecular weight 118, manufactured by FUJIFILM Wako Pure Chemical Corporation), 1.4 g of lithium nitrate (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 1.0 g of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) were mixed to prepare a slurry. A silicone rubber frame (4×4 cm, thickness 1 mm) was set on a PET sheet (8×8 cm, thickness 0.035 mm), and the prepared slurry was placed in the frame. Then, by using a hot plate, heating at 60°C for 1 hour to polymerize the polyethylene glycol diacrylate, a separation membrane was obtained. The weight average molecular weight (Mw) of the polymer of polyethylene glycol diacrylate is 1000. The separation membrane was removed from the frame and subjected to the test shown below.
[0117]
[0118] [Example 2]
[0119] In Example 1, a separation membrane was produced by the same method as in Example 1 except that diethyl carbonate was changed to ethylene glycol dimethyl ether (molecular weight 134, manufactured by FUJIFILM Wako Pure Chemical Corporation).
[0120] [Example 3]
[0121] In Example 2, a separation membrane was prepared in the same manner as in Example 2 except that the amount of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) added was changed to 0.1 g. The weight average molecular weight of the polymer of polyethylene glycol diacrylate was 10,000.
[0122] [Example 4]
[0123] In Example 1, a separation membrane was produced by the same method as in Example 1 except that diethyl carbonate was changed to monoethylene glycol dimethyl ether (molecular weight 32, manufactured by FUJIFILM Wako Pure Chemical Corporation).
[0124] [Example 5]
[0125] A slurry was prepared by mixing 6.0 g of a polymer represented by the following formula (4-1) (where r≈366, weight average molecular weight 10,000), 4.0 g of ethylene glycol dimethyl ether (manufactured by FUJIFILM Wako Pure Chemical Corporation), 1.4 g of lithium nitrate (manufactured by FUJIFILM Wako Pure Chemical Corporation), and 0.1 g of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation). A silicone rubber frame (4×4 cm, thickness 1 mm) was set on a PET sheet (8×8 cm, thickness 0.035 mm), and the prepared slurry was placed in the frame. Then, a separation membrane was obtained by heating at 60°C for 1 hour using a hot plate to crosslink the polymer represented by formula (4-1). The separation membrane was removed from the frame and provided to the test shown below.
[0126]
[0127] [Comparative Example 1]
[0128] In Example 2, a separation membrane was prepared by the same method as in Example 1 except that polyethylene glycol diacrylate was changed to one having a weight average molecular weight of 250 (manufactured by Sigma-Aldrich) and the amount of azobisisobutyronitrile (manufactured by FUJIFILM Wako Pure Chemical Corporation) added was changed to 2.0 g. The weight average molecular weight of the polymer of polyethylene glycol diacrylate was 500. As a result, a membrane could not be formed, and a separation membrane could not be obtained.
[0129] [Comparative Example 2]
[0130] In Example 1, a separation membrane was produced by the same method as in Example 1 except that diethyl carbonate was changed to pentaethylene glycol monomethyl ether (molecular weight 252, manufactured by FUJIFILM Wako Pure Chemical Corporation).
[0131] [Comparative Example 3]
[0132] In Example 5, a separation membrane was prepared in the same manner as in Example 5 except that the polymer represented by formula (4-1) was changed to a polymer represented by the following formula (10) (where r≈364 and weight average molecular weight 10,000).
[0133]
[0134] <Average pore diameter of separation membrane>
[0135] The average pore diameter of the separation membranes involved in the embodiments and comparative examples was measured by a gas adsorption method using argon. Specifically, a nitrogen adsorption measuring device (AUTOSORB-1, manufactured by Quantachrome Corporation) was used, and the average pore diameter was measured under the conditions of an evaluation temperature of 87K and an evaluation pressure range of a relative pressure (average pressure relative to saturated vapor pressure) less than 1. As shown in Tables 1 and 2, the average pore diameters of the separation membranes involved in the embodiments are all within 100 nm. More than and less than However, the average pore size of the separation membrane involved in the comparative example is within More than and less than outside the scope of.
[0136] <Evaluation of Solvent Separation Ability>
[0137] The separation membrane and separator (UP3085, manufactured by Ube Industries, Ltd.) involved in the examples or comparative examples were stacked and sandwiched between two sheets of silicone rubber (thickness 0.5 mm) and arranged between H-type units. Tetraethylene glycol dimethyl ether (molecular diameter 2.3 mm) was placed in the unit on the separation membrane side. ), visually observe the appearance of the separator after a specified number of days. If the separation membrane has excellent solvent separation ability, tetraethylene glycol dimethyl ether will not easily penetrate the separation membrane, and therefore tetraethylene glycol dimethyl ether will not easily penetrate into the separator, but if the separation membrane has poor solvent separation ability, tetraethylene glycol dimethyl ether will penetrate the separation membrane and penetrate into the separator. Therefore, the separation ability of the solvent (equivalent to the solvent of the first solvent and the second solvent) of the separation membrane can be evaluated by observing the appearance of the separator and confirming whether tetraethylene glycol dimethyl ether has penetrated into the separator. If tetraethylene glycol dimethyl ether has not penetrated into the separator after 1 day from the start of the test, it is indicated as "≥1 day" in Tables 1 and 2, and in this case, the solvent separation ability of the separation membrane can be said to be excellent. On the other hand, in Tables 1 and 2, if no penetration of tetraethylene glycol dimethyl ether is observed after 1 day, it is indicated as "<1 day". As shown in Tables 1 and 2, in the separation membranes according to Examples, tetraethylene glycol dimethyl ether did not permeate into the separator even after one day or more, but in the separation membranes according to Comparative Examples, tetraethylene glycol dimethyl ether permeated into the separator after one day.
[0138]
[0139] [Table 2]
[0140]
[0141] Explanation of symbols
[0142] 1-lithium ion secondary battery, 2-electrode group, 3-battery casing, 4-positive electrode collector sheet, 5-negative electrode collector sheet, 6-positive electrode, 7-separation membrane, 8-negative electrode, 9-positive electrode collector, 10-positive electrode mixture layer, 11-negative electrode collector, 12-negative electrode mixture layer.
Claims
1. A lithium ion secondary battery comprising a positive electrode mixture layer, a separator and a negative electrode mixture layer in this order, wherein: The positive electrode mixture layer contains a positive electrode active material, a first lithium salt and a first solvent. The negative electrode mixture layer contains a negative electrode active material, a second lithium salt, and a second solvent different from the first solvent. The separation membrane has an average pore size of More than and less than of pores, and The molecular diameters of the first solvent and the second solvent are above, The molecular diameter of the first solvent is calculated based on the theoretical bond length by finding the most stable structure of the solvent through density functional theory; and The average pore size of the separation membrane is measured by a gas adsorption method using argon gas at an evaluation temperature of 87 K and an evaluation pressure range of a relative pressure less than 1, and is calculated from the amount of argon gas adsorbed to the pores of the separation membrane.
2. The lithium ion secondary battery according to claim 1, wherein The separation membrane contains: a polymer of a compound having two or more polymerizable groups; and a lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group. The weight average molecular weight of the polymer is 800 or more, The molecular weight of the lithium ion conductive compound is 150 or less.
3. The lithium ion secondary battery according to claim 1, wherein The separation membrane contains a cross-linked product of polymers having a group represented by the following formula (1): In formula (1), R 1 represents an alkylene group having 1 to 6 carbon atoms, and * represents a bond.
4. A separation membrane, which is a separation membrane for being arranged between a positive electrode mixture layer and a negative electrode mixture layer in a lithium ion secondary battery having a positive electrode mixture layer and a negative electrode mixture layer, wherein the positive electrode mixture layer contains a positive electrode active material, a first lithium salt and a first solvent, and the negative electrode mixture layer contains a negative electrode active material, a second lithium salt and a second solvent different from the first solvent, The separation membrane has an average pore size of More than and less than of pores, and The molecular diameters of the first solvent and the second solvent are above, in, The molecular diameter of the first solvent is calculated based on the theoretical bond length by finding the most stable structure of the solvent through density functional theory; and The average pore size of the separation membrane is measured by a gas adsorption method using argon gas at an evaluation temperature of 87 K and an evaluation pressure range of a relative pressure less than 1, and is calculated from the amount of argon gas adsorbed to the pores of the separation membrane.
5. The separation membrane according to claim 4, comprising: a polymer of a compound having two or more polymerizable groups; and a lithium ion conductive compound having at least one group selected from the group consisting of a carbonyl group and a chain ether group, The weight average molecular weight of the polymer is 800 or more, The molecular weight of the lithium ion conductive compound is 150 or less.
6. The separation membrane according to claim 4, comprising a cross-linked product of polymers having a group represented by the following formula (1): In formula (1), R 1 represents an alkylene group having 1 to 6 carbon atoms, and * represents a bond.
Citation Information
Patent Citations
Lithium secondary battery
JP2001110447A
Battery members for secondary battery and secondary battery
JP2020170673A
Nanoporous polymer electrolyte
US20070218371A1